Effects of Ginseng Extract to The Plasma Level of Interleukin-8, COPD Assessment Test Scores, and Length of Hospitalization Acute Exacerbation of COPD Patients - Aslani Threestiana Sari; Suradi Suradi; Jatu Aphridasari (Jurnal Respirologi Indonesia, 2018)
Background: COPD exacerbations is an acute condition with worsening symptoms and require more intensive treatment changes. Increased inflammatory exacerbations marked increase in plasma levels of IL-8, exacerbation of clinical symptoms and risk of hospitalization. Ginseng extracts have anti inflammatory so it can be used as an additional drug in COPD exacerbations. Method: This study aimed to analyze the effect of ginseng extract on plasma levels of IL-8, CAT scores, and length of hospitalization of patients with COPD exacerbations. Clinical trials of experimental with pre test and post test design was conducted on 34 patients with COPD exacerbation in Dr. Moewardi Hospital Surakarta and Dr. Ario Wirawan Lung Hospital Salatiga from August until September 2016. Samples were taken by consecutive sampling were divided into two groups. The treatment group (n = 17) received standard therapy and ginseng extracts 2x100mg/day and the control group received only standard therapy (n = 17). Clinical improvement measured in CAT score and length of stay. Plasma levels of IL-8, CAT scores, and longer hospitalization time measured at entry and discharge criteria are met. Length of stay based on the number of days of care in hospitals. Results: There were significant difference (p=0.000) towards decreased of of IL-8 plasma level between treatment group (-12.38 ± 10,35pg/ml) and control group (0.65 ± 7,92pg/ml), towards decrease of CAT score (p=0.000) between treatment group (-16.53 ± 1.28) and control group (-12.59 ± 2.87), and length of stay (p = 0.004) between treatment group (4.29 ± 1.45) and control group (5.76 ± 1.20). Conclusions: The addition of ginseng extract 2x100 mg/day during hospitalization was significantly lowered plasma levels of IL-8, CAT scores, and shortening the length of stay. (J Respir Indo. 2018; 38: 192-8)